Integrating health intervention into existing program structure of the neglected tropical diseases: lessons learned from Yobe and Ebonyi states - Atobatele, Sunday; Sampson, Sidney; Jimoh, Akolade U.; Isiaka, Saheed D.; Ayodeji, Oluwafisayo; David, Joshua C.; Daniel, Victor; Dehinbo, Oluwafunmilayo (Frontiers in Public Health, 2024)
Nigeria has a national policy on neglected tropical diseases (NTD) which is coordinated by the Federal Ministry of Health and integrated into the health system at all government levels. A network of grassroots mobilizers, named community drug distributors (CDDs), deliver NTD drugs and commodities to rural and hard-to-reach communities throughout Nigeria. Interviews with state and local government coordinators of Nigerian NTD programs and focus group discussions with CDDs in Yobe and Ebonyi states were conducted to understand the working modalities of NTD programs in Nigeria to identify the potential of leveraging the NTD structure for additional health interventions such as COVID-19 vaccine rollouts. Collected data was coded and managed on NVivo version 12 using content analysis. The study found that the NTD committee had the following: a structured planning and coordination process, and a community mobilization approach for the effective delivery of routine Mass Administration of Medication (MAM) activities. Challenges encountered included little or no incentives for the CDDs, insecurity, transportation, and logistics, and lack of equipment and drug commodities. Nigerian NTD health structures have a wide reach, with a presence in all states and local government areas (LGAs), and this has previously been leveraged to deliver commodities and interventions to rural and hard-to-reach communities for non-NTD health programs and could thus be used similarly for COVID-19 vaccination programs. The enablers of integrating health interventions into the NTD structure are increased availability of finances and manpower, while lack of financial incentives and partners' buy-in were identified as possible. challenges. The study suggests that integrating COVID-19 interventions into the NTD program in Nigeria would be a significant accomplishment, as the existing structure can support future interventions. The study also highlights the efficiency of the NTD program's modalities and processes, indicating that an organized structural system for public health interventions can. increase the services of existing interventions while allowing for the integration of future interventions.